The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1128/iai.00556-19
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Activity of Human Group IIA Secreted Phospholipase A2in Relation to Enzymatic Hydrolysis of Oxidized Lipoproteins

Abstract: The level of human group IIA secreted phospholipase A2 (hGIIA sPLA2) is increased in the plasma of malaria patients, but its role is unknown. In parasite culture with normal plasma, hGIIA is inactive against Plasmodium falciparum, contrasting with hGIIF, hGV, and hGX sPLA2s, which readily hydrolyze plasma lipoproteins, release nonesterified fatty acids (NEFAs), and inhibit parasite growth. Here, we revisited the anti-Plasmodium activity of hGIIA under conditions closer to those of malaria physiopathology where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…Several sPLA 2 s, including sPLA 2 -IIF, -V and -X, which efficiently hydrolyze plasma lipoproteins to release free fatty acids, have the capacity to inhibit parasite growth in vitro, yet these sPLA 2 s are undetectable in human plasma. sPLA 2 -IIA, though hardly hydrolyzing normal lipoproteins, is increased in the plasma of malaria patients and hydrolyzes “oxidized” lipoproteins to block Plasmodium growth [ 26 ]. Injection of recombinant sPLA 2 -IIA into Plasmodium -infected mice reduces the peak of parasitemia when the level of plasma peroxidation is increased during infection.…”
Section: The Spla 2 Familymentioning
confidence: 99%
“…Several sPLA 2 s, including sPLA 2 -IIF, -V and -X, which efficiently hydrolyze plasma lipoproteins to release free fatty acids, have the capacity to inhibit parasite growth in vitro, yet these sPLA 2 s are undetectable in human plasma. sPLA 2 -IIA, though hardly hydrolyzing normal lipoproteins, is increased in the plasma of malaria patients and hydrolyzes “oxidized” lipoproteins to block Plasmodium growth [ 26 ]. Injection of recombinant sPLA 2 -IIA into Plasmodium -infected mice reduces the peak of parasitemia when the level of plasma peroxidation is increased during infection.…”
Section: The Spla 2 Familymentioning
confidence: 99%
“…Besides, melittin showed no toxicity in a study in vivo with mice that before treatment with melittin showed resistance to a lethal dose of influenza a virus [71]. At last, it has been also suggested using BV and, particularly, PLA2 as an antiparasitic agent in the treatment against some organisms such as Trypanosoma brucei brucei or Plasmodium falciparum [44,45].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Recent research by Dacheux et al [ 65 ] highlights that hGIIA’s role in host defense extends beyond anti-bactericidal properties to anti-malarial properties. Other sPLA 2 s human group IIF, hGV and hGX hydrolyze phospholipids present in lipoproteins producing non-esterified fatty acids such as polyunsaturated fatty acids that are highly toxic to the malaria pathogen, Plasmodium falciparum , however these sPLA 2 s are not detected in the plasma of infected patients [ 65 ]. Conversely, hGIIA has low affinity for these lipoproteins, but more effectively hydrolyses their oxidized counterparts, which are present in higher concentrations in plasma from malaria patients [ 65 ].…”
Section: Hgiia Functionmentioning
confidence: 99%
“…Other sPLA 2 s human group IIF, hGV and hGX hydrolyze phospholipids present in lipoproteins producing non-esterified fatty acids such as polyunsaturated fatty acids that are highly toxic to the malaria pathogen, Plasmodium falciparum , however these sPLA 2 s are not detected in the plasma of infected patients [ 65 ]. Conversely, hGIIA has low affinity for these lipoproteins, but more effectively hydrolyses their oxidized counterparts, which are present in higher concentrations in plasma from malaria patients [ 65 ]. hGIIA is up-regulated in the plasma of patients with malaria, catalyzes these oxidized phospholipids present in lipoproteins, promoting its parasite-killing effect [ 65 ].…”
Section: Hgiia Functionmentioning
confidence: 99%